Earnings Management in Borsa Istanbul During Seasoned Equity Offerings - Ashour, Mahmoud; Atik, Asuman (The Indonesian Capital Market Review, 2025)
To increase share prices during the issuance of seasoned equity shares, firms may be motivated to boost earnings through earnings management, particularly just before the offering. This study examines the earnings management practices of non-financial firms listed in Borsa Istanbul and surrounding seasoned equity offerings. Using the cross-sectional Modified Jones and Roychowdhury (2006) models, both accrual-based and real earnings management practices were analyzed from 2005 to 2018. The sample consists of 120 rights offerings within the research period. The results indicate that firms listed on Borsa Istanbul did not engage in earnings management the year before the offering. Instead, earnings management practices were observed in the year of the offering and the subsequent year. Additionally, other motivations may warrant further investigation, such as efforts to mitigate the negative impact of the offerings on stock performance after the offering.